Some Remarks on the Organization of Ottoman Society in the Early Modern Period: The Question of "Legal Dualism" and Societal Structures - Kursar, Vjeran (Array, 2010)
Organization of Ottoman society and its structures depended upon the configuration of Ottoman law, which was subdivided into two main spheres, i.e., Islamic and sultanic law. The state was guided by its own pragmatic interests and often neglected certain principles of Islamic law on behalf of sultanic law. However, the primacy of Islam and its essentials were never brought into question.